2019
DOI: 10.1093/toxsci/kfz145
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination and Management of Contaminated Hair following a CBRN or HazMat Incident

Abstract: This in vitro study evaluated the “triple protocol” of dry decontamination, the ladder pipe system (a method for gross decontamination), and technical decontamination for the decontamination of hair following chemical contamination. First, we assessed the efficacy of the 3 protocols, alone or in combination, on excised porcine skin and human hair contaminated with either methyl salicylate (MS), phorate (PHR), sodium fluoroacetate (SFA), or potassium cyanide (KCN). A second experiment investigated the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…For all interventions, substantial quantities of MeS and BeS remained in the hair following decontamination. This finding is consistent with previous in vitro studies where up to 50% of the tested chemical warfare agent (VX, sulphur mustard) or lipophilic chemical simulant (phorate or MeS) were found to be remaining in the hair following decontamination 16 , 19 , 31 . However, it is not consistent with a recent human volunteer field exercise from Chilcott et al 30 that demonstrated high decontamination efficacy for MeS contaminated hair.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For all interventions, substantial quantities of MeS and BeS remained in the hair following decontamination. This finding is consistent with previous in vitro studies where up to 50% of the tested chemical warfare agent (VX, sulphur mustard) or lipophilic chemical simulant (phorate or MeS) were found to be remaining in the hair following decontamination 16 , 19 , 31 . However, it is not consistent with a recent human volunteer field exercise from Chilcott et al 30 that demonstrated high decontamination efficacy for MeS contaminated hair.…”
Section: Discussionsupporting
confidence: 92%
“…Outputs of these studies have been informative and have led to changes to both UK and US emergency decontamination protocols for chemical incidents 14,15 . However, few studies have examined the effectiveness of current decontamination interventions in removing chemicals from hair 7,[16][17][18][19][20] and even fewer have done so with human volunteers 10,14,21 .…”
mentioning
confidence: 99%
“…Within the same manuscript, Matar et al (2019) also described the investigation of residual hair contamination after decontamination with “triple protocol” at different intervals post exposure, and the off gassing of hair after exposure to sulfur mustard or phorate (PHR) and subsequent decontamination, in order to assess the risk of secondary contamination. However, neither of these studies investigated dry decontamination on its own, and therefore, it is difficult to draw comparative conclusions about dry decontamination efficacy based on these aspects of the article.…”
Section: Resultsmentioning
confidence: 99%
“…Southworth et al (2020) found that the dry and wet decontamination protocol was superior to either dry or wet decontamination alone. Matar et al (2019) found that although the “triple protocol” was the most effective, this difference was only statistically significant when compared with dry decontamination alone (not compared with LPS or TD alone). These studies also highlighted that dry decontamination can often serve as the first step in these combination decontamination protocols, and they can be improvised, using common household/workplace/ambulance items while waiting for the deployment and arrival of specialist/formal decontamination supplies.…”
Section: Discussionmentioning
confidence: 99%
“…In response to exposures to toxic chemicals, disrobing will remove the majority of contamination from the casualties 10 . However, when exposed to liquid or solid compounds, decontamination is normally required to remove the toxic chemical from skin, hair and eyes 11,12 . In guidelines for immediate operational decontamination, procedures generally consist of disrobing and wet decontamination by showering, washing with soap and water or water only 12 .…”
Section: Introductionmentioning
confidence: 99%